Sustainable investing exchange-traded funds: US and European market - Adam Marszk (Journal of Economics and Management, 2019)
Aim/purpose – The key aim of the paper is to examine the diffusion of the sustainable investing Exchange-Traded Funds (ETFs) on the European and US ETFs markets, with the special focus on the market shares of sustainable investing and conventional funds. Design/methodology/approach – The model of diffusion of innovation (logistic growth model) is applied. Monthly data on the assets of ETFs in the time period of 2006-2017 are used. Findings – Increasing assets of sustainable investing ETFs were identified in both exam-ined regions. The average value of assets was higher in the United States, but the Euro-pean market became larger in the late 2017. Exclusively for Europe, the diffusion of sustainable investing ETFs was confirmed for the entire analysed time period as the market share of this category was increasing in relation to the conventional funds. In the United States, the diffusion was short-lived and took place in the time period 2006-2008. Research implications/limitations – Applied diffusion models assume an S-shaped trajec-tory of the innovation’s diffusion and the estimations are sensitive to historical data. Originality/value/contribution – It is the first study to apply the methodological framework of innovation diffusion for the examination of the sustainable financial prod-ucts. It addresses an issue of switching between sustainable investing and conventional financial products that has not been examined previously.